Moderating effects of a healthy lifestyle on the association of pre-metabolic syndrome with multiple chronic disease comorbidities - Youqiong Xu; Youqiong Xu; Xinchao Zhang; Xinchao Zhang; Jinxi Fang; Jinxi Fang; Wenchu Xu; Wenchu Xu; Qihui Chen; Qihui Chen; Yitao Zhu; Yitao Zhu; et al. (Frontiers in Public Health)
Studies have shown that healthy lifestyles reduce the risk of metabolic syndrome (MetS), but their impact on pre-metabolic syndrome (PreMetS) with multiple comorbidities remains unclear. To explore the association of PreMetS and MetS with multiple comorbidities and to assess whether a healthy lifestyle influences these associations. Associations between PreMetS and MetS, lifestyle behaviors and multiple comorbidities were analyzed by univariate and multivariate logistic regression. The moderating effect of healthy lifestyle was assessed by stratified analyses. Integrate healthy lifestyles and explore their association with multiple comorbidities using normal metabolism and healthy lifestyles as reference groups. PreMetS [OR = 1.38, 95%CI: 1.16–1.64] and MetS [OR = 1.61, 95%CI: 1.32–1.97] were associated with a significantly higher risk of multiple comorbidities compared with the normal population, and the risk of multiple comorbidities tended to increase as the number of metabolic disorder components increased (p < 0.001). Adherence to a healthy lifestyle (favorable [OR = 0.69, 95%CI: 0.59–0.82] and extremely favorable [OR = 0.54, 95%CI: 0.43–0.68]) was associated with a reduced risk of multiple comorbidities, with a trend toward a decreased risk of multiple comorbidities as the number of healthy lifestyles increased (p < 0.001). PreMetS was not associated with multiple comorbidities in healthy lifestyles (moderate and above) (p > 0.05), whereas MetS remained an associated risk factor for multiple comorbidities (p < 0.05). Compared to healthy lifestyle normometabolic subjects, unfavorable lifestyle PreMetS subjects were associated with increased risk of multiple comorbidities [OR = 2.05, 95%CI: 1.30–3.23], whereas healthy lifestyle PreMetS subjects were not associated with increased risk of multiple comorbidities [OR = 1.52, 95%CI: 0.93–2.50]. Metabolic profiles and lifestyle factors were independently associated with multiple comorbidities, and a healthy lifestyle counteracted the deleterious effects of PreMetS on the risk of multiple comorbidities in adults in Fuzhou. However, population homogeneity and recall bias resulting from the study design may lead to reverse causality and residual or unknown confounding factors.